Big win: Trees on agricultural land sink four times more carbon - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
Recent studies show that carbon sequestered by trees on agricultural land is not well accounted for. If it was, researchers argue in a new study: “Global Tree Cover and Biomass Carbon on Agricultural Land: The contribution of agroforestry to global and national carbon budgets,” total carbon estimates from agricultural land could be more than four times higher.